Cross-Cultural Analysis of Turn-Taking Practices in English and Spanish Conversations - Claudia B Martínez (Vernacular: New Connections in Language, Literature, & Culture, 2018)
Conversation analysis is primarily concerned with the tacit rules of turn-taking in standard systems of conversation—that is, with how people maneuver through spoken conversations to make themselves heard, while still allowing for dialogue to take place. Sacks, Schegloff & Jefferson had largely influenced the groundwork for this field in the late 1970s by setting forth certain proprieties of speech that deem overlaps, or interruptions, generally untoward and counterproductive. My goal here is to rethink this theory, however, to illuminate certain culturally specific instances of overlapping that do indeed lend themselves to the flow of the conversation. I compare such instances as they have occurred in four conversations altogether unrelated with one another: two spoken in American English and two in Spanish of a variety of dialects—Venezuelan, Honduran, Mexican, and Panamanian. In this light, I isolate nuances of cooperative and interruptive overlaps, highlighting the attempts at floor-taking as they differ from English to Spanish as well as noting how certain strategies remain the same as universal modes of turn-taking. I note a tendency for hispanohablantes to lengthen certain monosyllabic overlaps—such as aja, si, and mmm —in not just acknowledging but actually reinforcing the conversational prerogative of their speaking partners. This study is of particular value to conversation analysts because it proposes reconstruction of the lens through which they observe cultural speaking habits in both English- and Spanish-speaking communities, thereby potentially reforming the definitions currently in place and calling for similar studies with regard to other languages.
Keywords: linguistics; Spanish; turn-taking; conversation; analysis; overlaps